Model Analysis Of Consumer Behavior: Cultural Factors, Personal Factors and Social Factors On Online Store Consumers (E-Commerce) - Muthia Salsabila Budiman; BJ. Aldo; Heri Sofwan; Pino Alexander (Greenation International Journal of Economics and Accounting, 2023)
This study aims to determine the factors that influence consumer behavior. Previous research or relevant research really functions to strengthen theory and also the phenomenon of the relationship or influence between variables. Writing this scientific article is a qualitative method and literature review which helps to obtain various descriptions through the factors that influence the results of the variables studied. This article reviews the factors that influence consumer behavior, namely: cultural factors, social factors and personal factors, a study of the Human Resource Management literature. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) cultural factors influence consumer behavior; 2) social factors influence consumer behavior; and 3) personal factors influence consumer behavior.